Gastronomic Paradigms in Contemporary Western Cuisine: From French Haute Cuisine to Mass Media Gastronomy - del Moral, Raimundo G. (Frontiers in Nutrition, 2020)
Thomas Kuhn brings the concept of "paradigm" as the fundamental engine in the progress of humanity. Kuhn defines paradigms as the set of formal theories, experiments and work methods that define a process (scientific, economic, social and in this case, contemporary haute cuisine), in a given time. According to Kuhn, progress does not happen by gradual accumulation of knowledge, but rather by abrupt advances. In this review, the conceptual evolution experienced by contemporary gastronomy (from the French Revolution to today) is analyzed applying the paradigm structure in light of the scientific knowledge of each era. It is thus reviewed how the first and second gastronomic paradigms, proposed respectively by Carême and Escoffier and based on food smell and taste the first and the flavor of the sauces the second, have been replaced by the third and fourth paradigms, led respectively by the Nouvelle Cuisine in France and Ferrán Adriá in Spain, and in whose development touch, sight and sound have become increasingly prominent in gastronomic pleasure. Finally, it is analyzed how new trends in gastronomy: 1) worldwide diffusion of the Spanish tapas; 2) globalization of ethnic and fusion cuisines; 3) the growing disappearance of the professional gastronomic critique and its replacement by mass media influencers; 4) the increase of sustainability in cooking with development of local-, vegan- and paleo-cooking, comfort and smart food and finally, 5) the growing role of social networks and the self-itis linked to photography or foodstagramming in the gastronomic experience are leading towards a new gastronomic paradigm based on the global socialization of classic gastronomy.